The earliest evidence of damselfly-like endophytic oviposition in the fossil record - Laaß, Michael; Hoff, Corinna (Lethaia, 2015)
The reproductive strategy of insects of inserting eggs into plant tissue (endophytic oviposition) is known from the Late Carboniferous onwards. The earliest known ovipositional scars are large, that is up to 38 mm long, and irregular both in size and in shape, and they are not arranged in a regular pattern. Oviposition patterns resembling those of present-day Odonata are first reported from the Late Palaeozoic. These egg cavities are generally of smaller size and have a regular oval shape. They are usually arranged in longitudinal rows or in a zigzag configuration. The most likely tracemakers were gracile damselfly-like insects such as the Archizygoptera, a group closely related to modern Zygoptera. In this paper, the earliest evidence of endophytic oviposition resembling the ‘Coenagrionid Type’ of Odonatoptera is described. It derives from the Wettin member of the Siebigerode Formation of the Saale-Basin in Central Germany (Upper Carboniferous, Gzhelian) and consists of about 49 elliptical scars with lengths of about 2 mm, probably deposited on a leaf of Cordaites. The arrangement of the scars in short transverse rows, their regular size and elliptical shape suggest that the tracemaker was probably a member of the extinct odonatopteran suborder Archizygoptera. If so, the tracefossil described here would be the earliest evidence for this endophytic oviposition in an ancestral group of modern Zygoptera.